Opening up the cartographic heritage of the Spanish Geographical Institute by means of publishing standardized, Inspire compatible metadata - Capdevila Subirana, Joan; Sánchez Maganto, Alejandra; Camacho Arranz, Elena; Arístegui Cortijo, Andrés (LIBER Quarterly: The Journal of the Association of European Research Libraries, 2013)
By making the most of the versatility that the Internet provides, and following the latest guidelines developed by the European Union through the Inspire and PSI Directives, the Spanish Geographical Institute has been undertaking in the last few years the release of geographic information in a free and interoperable way. Essential factors for this task are both creating metadata to describe and better use that information, and applying standards, both in the data model and in the web services. In this piece of work we will explain the application of these principles on the historical information held in the Technical Archive of the Spanish Geographical Institute. We will present the recent publication of 120,000 metadata records described as ISO (NEM model), which can be accessed through an Inspire compliant discovery service. This service is interrogated by an open source software catalogue client developed by the Spanish Geographical Institute.